Dependence at a distance: Labour mobility and the evolution of the single industry town. (21st December 2017) - Storey, Keith; Hall, Heather
Abstract : The single industry town (SIT) is a fundamental feature of the Canadian economy and landscape. However, changes in the demands for and availability and mobility of labour, together with changing attitudes of companies, governments, and labour towards SITs, have resulted in some significant changes in the nature of SITs in recent decades. No new purpose‐built resource town has been constructed in Canada since Tumbler Ridge in the 1980s; instead new resource developments in remote areas are characterized by a mobile workforce residing permanently at a distance from the resource, and commuting on a rotational basis to and from camps established near that resource. These work arrangements have had the advantage of dissipating the community effects of resource cycle booms and busts as the workforce is geographically dispersed. However, this changed in the recent commodity boom when labour was targeted from specific regions and communities far from the resource, creating a form of "dependence at a distance" and a new type of SIT. Based on the experience of oil sands developments in the Regional Municipality of Wood Buffalo in Northern Alberta, and using Fort McMurray to illustrate the evolution of the traditional SIT and the towns on the Burin Peninsula in Newfoundland as examples of the new dependent‐at‐a‐distance SITs, this paper describes the change process and considers some of the policy implications that these changes present. Key Messages: Commute work has created a new settlement phenomenon—resource dependent‐at‐a‐distance communities. As with traditional single industry towns, dependent‐at‐a‐distance communities are vulnerable during resource downturns. New policies are required to address the problems faced by dependent‐at‐a‐distance communities.